Source of Authority for Implementing Educational Supervision - Wulan Oktarina; Aisyah Khairunnisa; Resti Utami; Ellen Okta Divy; Kasinyo Harto; Choirun Niswah (Edumaspul: Jurnal Pendidikan, 2023)
Various educational problems in Indonesia can be studied by supervising education. Educational supervision is a process of assistance and support given to teachers in developing their abilities consisting of knowledge, skills, and creativity in teaching and commitment or motivation as a teacher. This study aims to examine and describe the source of authority for implementing educational supervision. This research is a literature study research. The results of this study state that in its implementation, the source of authority for the implementation of educational supervision in schools is carried out by the Principal or school supervisor, called a supervisor, who serves as a supervisor and controller of teacher performance. This supervision and control is carried out so that the teacher does not deviate from the role of teacher or educator. Based on the National Education System Law No. 20 of 2003, the principal or school supervisor supervises to ensure the effectiveness and efficiency of learning. In this case, the principal or school supervisor is an illustration that a supervisor must have an official position that has authority or authority in supervising education.